The essence and structure of competence art of a future music teacher (Pedagogy of Higher and Secondary Education, 2006)
The article coven пен requirements to training of future music teacher in the system of higher education. The article highlights the essence and structure of competence art offuture music teacher, peculiarities of its formation in the process of training the fortepiuno playing.
Keywords: competence art future music teacher; training the fortepiano playing; system of higher education